MAXIMUM POWER POINT TRACKING UNTUK WIND TURBINE - Rifqy Adrian; Dori Oktariandi; Eko Sulistyo; Ocsirendi Ocsirendi (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
The electrical energy produced by wind power plants depends on the wind speed and the number of blades in the wind turbine. Both of these causes the wind turbine output power curve to be non-linear, because this non-linearity causes the energy that enters the windmill not to be fully utilized. One way to maximize wind turbine output is to find the maximum point on the wind turbine. The goal that must be achieved in this final project is to be able to find the maximum point on the wind turbine, maximum power point tracking (MPPT) using the perturbe and observe (PO) algorithm with the type of load resistor and be able to display the current and voltage values ​​on the serial monitor and store the current values. and the voltage on the SD card. In the test results on this tool using a load resistor of 20 ohms, it was found that the maximum voltage value read was 6.28v and the maximum current was 0.12A with a maximum power of 0.78 Watt.